2013
DOI: 10.1007/s00264-013-1826-4
|View full text |Cite
|
Sign up to set email alerts
|

Tourniquet time affects postoperative complications after knee arthroplasty

Abstract: Tourniquet time over 100 minutes increases the risk of complications after knee arthroplasty surgery and special attention is advocated to reduce the tourniquet time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 22 publications
1
67
0
2
Order By: Relevance
“…Operative time did not differ between limbs assigned to the tourniquet procedure (62 ± 11 minutes) and limbs assigned to the notourniquet procedure (65 ± 10 minutes). As expected, the average tourniquet time in the tourniquet group was greater than the no-tourniquet group (group difference = 42 minutes [95% CI, [37][38][39][40][41][42][43][44][45][46][47]; p \ 0.001).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Operative time did not differ between limbs assigned to the tourniquet procedure (62 ± 11 minutes) and limbs assigned to the notourniquet procedure (65 ± 10 minutes). As expected, the average tourniquet time in the tourniquet group was greater than the no-tourniquet group (group difference = 42 minutes [95% CI, [37][38][39][40][41][42][43][44][45][46][47]; p \ 0.001).…”
Section: Resultssupporting
confidence: 63%
“…Advantages of tourniquet use include improved visualization, reduced intraoperative blood loss, and enhancement of cement fixation [11,14,17,21,22,27,45,54]. Reported adverse effects of tourniquet use include reduced early knee flexion [11,14,60,62,65], increased perioperative pain [11,14,27,56], postoperative limb swelling [11,21,47], wound complications [9,12,40,41], and creation of cardiac and cerebral microemboli [16,20,[42][43][44]55]. Additionally, some have reported an increased incidence of deep venous thrombosis [8,57,65], arterial thrombosis in subjects with preoperative vascular disease [26,48,49], and peripheral nerve injury [28,39].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, its use for more than an hour during TKA increases the risk for local arterial and venous thrombosis [15]. Meanwhile, the introduction of modern cementing techniques and the use of tranexamic acid may obviate the need for a tourniquet during TKA [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been recommended that TT be limited to 2 h in human studies due to the increase in postoperative complications caused by an extended TT [10]. Investigating the relationship between TT and postoperative complications in arthroplastic knee surgery, Olivecrona et al [17] found an increase in postoperative complications including wound leakage, local injury due to TP, nerve damage, compartment syndrome, deep venous thrombosis, and pulmonary embolism with every 10-min increment in TT.…”
Section: Discussionmentioning
confidence: 99%